Reduced Bone Mineral Density in Children and Adolescents: Causes, Incidence and Treatment - S. V. Maltsev; G. Sh. Mansurova ("Paediatrician" Publishers LLC, 2015)
Osteoporosis in children is an urgent problem, since it occurs at different ages. The main risk factors and causes of primary and secondary osteoporosis in children include exogenous and endogenous, modifiable and non-modifiable factors. Critical age periods of childhood characterized by a high risk of reduced bone mineral density and fractures are specified. The article describes the biological effects of calcium, vitamin D and osteotropic trace elements and shows their role in osteogenesis and bone remodeling. It also presents the results of the study of reduced bone mineral density in children, the data on the availability of vitamin D for children at different ages, and provides recommendations for treatment.